Pengaruh Edukasi terhadap Pengetahuan tentang Perilaku Hidup Bersih dan Sehat (PHBS) Siswa SDN 104 Kendari - Elsa Elsa; Hartati Bahar; La Ode Ahmad Saktiansyah (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Clean and Healthy Behavior (CHB) is an essential aspect of improving public health, particularly among school-aged children. At SDN 104 Kendari, there are still challenges related to students’ behavior, especially the habit of buying snacks from unregulated vendors near the school, which increases the risk of exposure to foodborne diseases. This study aims to examine the effect of health education on students’ knowledge of CHB. The research employed a quantitative approach with a quasi-experimental design using a one-group pre-test and post-test method. The sample consisted of 42 students, selected through stratified random sampling to ensure representation across different classes and initial knowledge levels. The research instruments included pre-test and post-test questionnaires to measure students’ knowledge, complemented by educational videos designed to be engaging and informative, enhancing students’ understanding of CHB principles. Results indicated that prior to the educational intervention, the majority of students’ knowledge was categorized as sufficient (57.1%) and good (42.9%). Following the intervention, there was a significant increase in knowledge, with 69% of students categorized as good, reflecting improved understanding of CHB principles. Statistical analysis using a paired sample t-test revealed a significant effect of the educational intervention on students’ knowledge of CHB (p-value <0.05). These findings highlight that health education through video media is an effective strategy to enhance students’ knowledge of CHB and promote healthy behaviors within the school environment. The implementation of audiovisual-based educational programs can be recommended as part of ongoing school health activities and sustainable promotive-preventive efforts.